HLA-transgenic mouse models to study autoimmune central nervous system diseases - Kyle R. Pressley; Lance Schwegman; Maria Montes De Oca Arena; Carol Chase Huizar; Scott S. Zamvil; Thomas G. Forsthuber (Taylor & Francis Group, 2024)
It is known that certain human leukocyte antigen (HLA) genes are associated with autoimmune central nervous system (CNS) diseases, such as multiple sclerosis (MS), but their exact role in disease susceptibility and etiopathogenesis remains unclear. The best studied HLA-associated autoimmune CNS disease is MS, and thus will be the primary focus of this review. Other HLA-associated autoimmune CNS diseases, such as autoimmune encephalitis and neuromyelitis optica will be discussed. The lack of animal models to accurately capture the complex human autoimmune response remains a major challenge. HLA transgenic (tg) mice provide researchers with powerful tools to investigate the underlying mechanisms promoting susceptibility and progression of HLA-associated autoimmune CNS diseases, as well as for elucidating the myelin epitopes potentially targeted by T cells in autoimmune disease patients. We will discuss the potential role(s) of autoimmune disease-associated HLA alleles in autoimmune CNS diseases and highlight information provided by studies using HLA tg mice to investigate the underlying pathological mechanisms and opportunities to use these models for development of novel therapies.